Organ Donation and Transplantation Current Status and Future Challenges - Tsoulfas, Georgios (IntechOpen, 2018)
One of the most interesting and at the same time most challenging fields of medicine and surgery has been that of organ donation and transplantation. It is a field that has made tremendous strides during the last few decades through the combined input and efforts of scientists from various specialties. What started as a dream of pioneers has become a reality for the thousands of our patients whose lives can now be saved and improved. However, at the same time, the challenges remain significant and so do the expectations. This book will be a collection of chapters describing these same challenges involved including the ethical, legal, and medical issues in organ donation and the technical and immunological problems the experts are facing involved in the care of these patients.The authors of this book represent a team of true global experts on the topic. In addition to the knowledge shared, the authors provide their personal clinical experience on a variety of different aspects of organ donation and transplantation.